A Mixed-Methods Exploration of the Role and Impact of Stigma and Advocacy on Substance Use Disorder Recovery. Issue 4 (2nd October 2019) - Ashford, Robert D.; Brown, Austin M.; Canode, Brent; McDaniel, Jessica; Curtis, Brenda
ABSTRACT: Obstacles to intrapersonal and interpersonal growth, due to stigma and discrimination, may constitute a significant challenge to those in recovery. Engaging in recovery-related advocacy may serve as a buffer to the experience of stigma and discrimination. The purpose of this pilot study is to examine whether the perception of stigmatization is associated with common recovery measures such as recovery capital, self-esteem, and self-efficacy, as well as to explore the role of advocacy for individuals in recovery through thematic analysis. Statistically significant results suggest that individuals who believe they are stigmatized have less recovery capital and self-esteem than those who do not hold this belief. Several major themes related to the overall impact, perceived benefits, and perceived harms of engaging in advocacy emerged from the thematic analysis such as reduction in stigma, improving soft skills, service to others, and reduced ability to engage in self-care. Findings suggest that individuals who believe they are stigmatized have lower functional outcomes (recovery capital and self-esteem) and mitigating these effects may be important for future recovery success. Additionally, thematic results suggest that engaging in recovery related advocacy offers a multitude of potential benefits and positive impacts, but also may have important potential harms to consider.